Exploring Students’ Competences in Building Effective Online Learning during COVID-19 Pandemic - Farani, Rizki (Journal of English and Education (JEE), 2023)
COVID-19 outbreak has caused some significant learning issues for students, such as internet connections, digital competence, heavy workloads, distraction, and difficult time management. However, there is still limited exploration on how students survived in online learning. To fill the void, this study aims to explore specifically how students completed their assignments in pandemic. The method focused on discourse content analysis to investigate students’ personal reflection. There were 22 undergraduate students who shared their reflective notes as main data. Supporting data were obtained from observation in Zoom meeting, WhatsApp group and Google Classroom. All data were analyzed by using COVID-19 Online Learning (CoOL) conceptual framework which includes three inputs: 1) students’ interaction, 2) instructors’ course design and 3) institutions’ facilities. Based on the results, interaction and course design play a significant role in achieving learning goals. They created a careful plan, studiedindependently, collaborated with peers, and consulted their work to the teachers. At the end of the semester, they gained new insight about knowledge and teamwork skills. In conclusion, students were able to survive online learning during the pandemic. Furthermore, teachers’ role is to enhance their effort by providing guidelines and feedback.